2021
DOI: 10.1590/s1678-3921.pab2021.v56.01882
|View full text |Cite
|
Sign up to set email alerts
|

Productive potential and quality of pitaya with nitrogen fertilization

Abstract: The objective of this work was to determine adequate rates of nitrogen to reach satisfactory yield, fruit quality, and cladode nutrient content in three species of pitaya. The experimental design was carried out in randomized complete blocks, with a 3×4 factorial arrangement. The treatments consisted of the following pitaya species and N rates: Selenicereus megalanthus, Hylocereus undatus, and Hylocereus polyrhizus; and 0, 50, 100, and 200 g N per plant, in the first production cycle (2016/2017 crop season) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The content of TSS indicated that more fruit sweetness produced a higher 0 Brix and a progressive increase in N and P doses applied in this study showed no significant difference in TSS parameter was observed (Table 3). Alves et al (2021) showed that soluble solid parameter revealed no effect as a result of N fertilizer application on Hylocereus polyrhizus, Hylocereus undatus, and Selenicereus megalanthus variety from the first to the third production cycle. A similar trend was reported by Gonzaga et al (2017) showed that there was a negative effect on TSS parameters as a result of nitrogen application and NPK application led to the production of sucrose or soluble solid content reduced due to high nitrogen fertilizer applied.…”
Section: Effect Of Nitrogen and Phosphorus Fertilizer On Yield And Fr...mentioning
confidence: 95%
See 1 more Smart Citation
“…The content of TSS indicated that more fruit sweetness produced a higher 0 Brix and a progressive increase in N and P doses applied in this study showed no significant difference in TSS parameter was observed (Table 3). Alves et al (2021) showed that soluble solid parameter revealed no effect as a result of N fertilizer application on Hylocereus polyrhizus, Hylocereus undatus, and Selenicereus megalanthus variety from the first to the third production cycle. A similar trend was reported by Gonzaga et al (2017) showed that there was a negative effect on TSS parameters as a result of nitrogen application and NPK application led to the production of sucrose or soluble solid content reduced due to high nitrogen fertilizer applied.…”
Section: Effect Of Nitrogen and Phosphorus Fertilizer On Yield And Fr...mentioning
confidence: 95%
“…Boyd et al (2013), Donno et al (2013) and Kozera et al (2013) revealed that fruit yield and quality increased as affected by N and P fertilizers applied. N fertilizer application improved yield and fruit quality on three species of dragon fruit (Hylocereus polyrhizus, Hylocereus undatus and Selenicereus megalanthus) was reported by Alves et al (2021).…”
Section: Effect Of Nitrogen and Phosphorus Fertilizer On Yield And Fr...mentioning
confidence: 96%
“…Pitaya plants at 2–3 months need no fertilizer; at 1 year, they need 4 ounces of inorganic fertilizers at a 6-6-6 or 8-3-9 ratio from early spring to winter, along with 4 pounds of manure or compost per plant in summer; at 2–3 years, need 5 to 6 ounces of inorganic fertilizers at the same ratio, along with 6 pounds of manure or compost per plant in summer; and at 4 or move years, need 8 to 12 ounces of inorganic fertilizers, along with 5 pounds of manure or compost per plant in both spring and mid-summer [ 111 , 119 , 120 ]. Some studies suggest 1.2 kg fertilizer ratio of N:P:K:Mg (9.6:4.8:17.6:2.4) and 12 kg compost per plant per year [ 121 ], 45 t/ha organic fertilizer +3% biochar [ 122 ], 44–67 mg/dm 3 of phosphorus in the soil [ 123 ], 170–300 g of nitrogen per plant [ 124 ], 9 kg of steer manure with 3.5 ounces of 13-13-13 fertilizer/plant [ 111 ], and N-P-K at 46-0-0, 24-24-0 and 16-16-16 [ 125 ] to pitaya plants.…”
Section: Agronomy Cultivation Pests and Diseasesmentioning
confidence: 99%
“…In research studies, variation in productivity has been attributed to the uneven size of fruits, demonstrating that the number of fruits per plant is related to its composition, quality and productivity (Fernandes et al, 2018;Rabelo et al, 2020a;Rabelo et al, 2020b;Alves et al, 2021).…”
Section: Introductionmentioning
confidence: 99%